Environmental friendly pervious concrete with slag as cement replacement material - Neo, Derek Huai Wang (2011)
Over the years, the use of pervious concrete is becoming more popular and accepted in developed countries as low-volume pavement construction such as parking lots, residential roads, pathways and etc. Pervious concrete is being used more frequently due to its benefits in reducing the quantity of runoff water, improving water quality, enhancing pavement skid resistance during storm events by rapid drainage of water, and reducing pavement noise.